PENERAPAN PRINSIP-PRINSIP FILSAFAT PROGRESIVISME DALAM MENGATASI PERMASALAHAN-PERMASALAHN GURU MENGHADAPI SISWA BERKEBUTUHAN KHUSUS DI SEKOLAH INKLUSI - Yuliansyah, Arief; Syihabuddin; Maulia Depriya Kembara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine the role of progressivism in overcoming the problems of teachers in dealing with students with special needs in inclusive schools. This study uses the Systematic Literature Review (SLR) method referring to PRISMA (Preferred Reporting Item for Systematic Review and Meta-Analysis) to examine documents from Google Scholar between 2010 and 2024 related to the application of the philosophy of progressivism in education and also related to the problems of teachers in dealing with children with special needs (ABK).Searching for journal articles using Publish or Perish with the keyword philosophy of progressivism in learning students with special needs. Then we also conducted a search on Publish or Perish related to the problems of teachers facing children with special needs with the keywords teacher problems facing students with special needs. From these two journal searches, it turns out that the principles of the philosophy of progressivism, which prioritize aspects of contextual and student-centered learning, can overcome teachers' problems in dealing with students with disabilities related to lesson plans, learning methods and media and infrastructure.